Mitigating grain growth in fully stabilized zirconia via a two‐step sintering strategy for esthetic dental restorations. Issue 2 (21st September 2022) - Kim, Boo Kyung; Yun, Jong Hyuk; Jung, Wook Ki; Lim, Chek Hai; Zhang, Yu; Kim, Do Kyung
Abstract: Overall, 8‐mol% yttria‐stabilized zirconia (8YSZ), unlike 3YSZ, is optically transparent and stable against low‐temperature degradation but has insufficient mechanical properties due to its large grain size. The influence of the grain size of 8YSZ on mechanical properties was investigated to develop an 8YSZ suitable for dental restoration. Modulation of the grain size and relative density was achieved via a two‐step sintering (TSS) process, and the corresponding kinetic window was established. The conditions of TSS employed herein yielded a relative density of more than 99% while maintaining a small grain size of 0.75 µm. On the other hand, the highest biaxial strength and the highest total transmittance attained were 833 MPa and 34.6% (1‐mm‐ thick, 39.1% for a 0.5‐mm thick sample) in the TSS 8YSZ with a grain size of 1.25 µm. These results suggest that strength has improved only when grain size reduction and increased relative density are achieved at the same time. The results demonstrate that the ceramic processing method has a significant effect on the mechanical and optical properties of 8YSZ needed for dental restoration and provide a new insight that contrasts previous studies focused on the starting material.